DPP-4 inhibition protects human umbilical vein endothelial cells from hypoxia-induced vascular barrier impairment - Naoko Hashimoto; Kento Ikuma; Yui Konno; Masanori Hirose; Hiroyuki Tadokoro; Hiroshi Hasegawa; Yoshio Kobayashi; Hiroyuki Takano (Elsevier, 2017)
Dipeptidyl peptidase-4 (DPP-4) inhibitors are relatively new class of anti-diabetic drugs. Some protective effects of DPP-4 on cardiovascular disease have been described independently from glucose-lowering effect. However, the detailed mechanisms by which DPP-4 inhibitors exert on endothelial cells remain elusive. The purpose of this research was to determine the effects of DPP-4 inhibitor on endothelial barrier function. Human umbilical vein endothelial cells (HUVECs) were cultured and exposed to hypoxia in the presence or absence of Diprotin A, a DPP-4 inhibitor. Immunocytochemistry of vascular endothelial (VE-) cadherin showed that jagged VE-cadherin staining pattern induced by hypoxia was restored by treatment with Diprotin A. The increased level of cleaved β-catenin in response to hypoxia was significantly attenuated by Diprotin A, suggesting that DPP-4 inhibition protects endothelial adherens junctions from hypoxia. Subsequently, we found that Diprotin A inhibited hypoxia-induced translocation of NF-κB from cytoplasm to nucleus through decreasing TNF-α expression level. Furthermore, the tube formation assay showed that Diprotin A significantly restored hypoxia-induced decrease in number of tubes by HUVECs. These results suggest that DPP-4 inhibitior protects HUVECs from hypoxia-induced barrier impairment.